PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN USAHA TANI PADI SAWAH (Studi di Desa Baru Tahan Kecamatan Moyo Utara) - A Asmini; Wahyu Haryadi; Muhammad Jamta (Jurnal Ekonomi & Bisnis, 2020)
This study aims to know the role of farmer groups in increasing rice farming income in Baru Tahan Village, Moyo Utara sub-district year of 2018-2019. This study was a descriptive. The type of data in this study was qualitative data. Sources of data in this study were primary and secondary. The populations in this study were Seventeen of farmers groups in Baru Tahan Village. The sampling technique used in this study was the Snowball sampling technique. The numbers of samples were 9 from farmers group and 4 from Baru Tahan government. The analysis technique used in this study was qualitative data analysis, which consisted of data collection, data reduction, data presentation and conclusions. Based on the results of study showed that the role of farmers groups that were greatly felt by members of farmers group and the communities in increasing the income of rice farming in Baru Tahan Village, Moyo Utara district was as a medium of instructor and information, procurement of seeds, recipients of fertilizers and farming tools.